Arqueologia dos monumentos da Pré-história recente : algumas sugestões interpretativas - Jorge, Vítor Oliveira (2002)
In this paper, the author calls attention to a marked contrast between two different kinds of architectural behaviour in the later prehistory of the north of Portugal. In the middle/ later neolithic, groups of barrows (each one containing a "megalithic" passage grave) started to transform the landscape. But these necropolis were "modular" - monuments could be built one by one, in an "additive logic". On the contrary, in the copper and earlyl middie bronze ages, entire hills with precincts, platforms, etc, were conceived as devices made to see the landscape, and to be seen from afar, as symbois of the identity of each regional group. The paper underlines the importance of an archaeology of prehistoric architecture, including the ways people organised their space in the past, be it considered at a micro scale (structure, part of a site, etc.) or at a macro scale (a river basin, for instance).